Anal squamous cell carcinoma: Impact of radiochemotherapy evolution over years and an explorative analysis of MRI prediction of tumor response in a mono-institutional series of 131 patients - Bonù, Marco Lorenzo; La Mattina, Salvatore; Singh, Navdeep; Toraci, Cristian; Spiazzi, Luigi; Terraneo, Fabrizia; Barbera, Fernando; Vitali, Paola; Frassine, Francesco; Guerini, Andrea; Triggiani, Luca; Tomasini, Davide; et al. (Frontiers in Oncology, 2022)
INTRODUCTION Radiochemotherapy (RTCHT) for the treatment of anal squamous cell carcinoma (ASCC) evolved dramatically, also thanks to intensity modulated RT (IMRT) and 3D image guidance (3D IGRT). Despite most patients presents fair outcomes, unmet needs exist. Predictors of poor tumor response are lacking; acute toxicity remains challenging and local relapse remains the main pattern of failure. PATIENTS AND METHODS ASCC stage I-III treated with 3D conformal radiotherapy or IMRT and CDDP-5FU or Mytomicine-5FU CHT between 2010 and 2020 were included. Study endpoints included freedom from locoregional recurrence (FFLR), colostomy free survival (CFS), freedom from distant metastasis (FFDM), overall survival (OS), acute and late toxicity scored with Common terminology criteria for adverse events 5.0 (CTCAE). An exploratory analysis was performed to identify possible radiomic predictors of tumor response. Feature extraction and data analysis were performed in Python ™ while other statistics were performed using SPSS® v.26.0 software (IBM®). RESULTS 131 patients were identified. After a median FU of 52 months, 83 pts (63,4%) were alive. 35 pts (26,7%) experienced a locoregional failure, while 31 pts (23,7%) relapsed with distant metastasis. Five years FFLR, CFS, DMFS, OS resulted 72,3%, 80,1%, 74,5% and 64,6%. At Multivariate analysis, 2D IGRT was associated with poorer FFLR, OS and CFS (HR 4.5, 4.1, 5.6, respectively); 3DcRT was associated with poorer OS and CFS (HR 3.1, 6.6, respectively). IMRT reduced severe acute gastro-intestinal (GI) and severe skin acute toxicity in comparison with 3DcRT. In the exploratory analysis, the risk of relapse depended on a combination of the three parameters, Total Energy, Gray Level Size Zone Matrix’s Large Area High Grey Level Emphasis (GLSZM’s LAHGLE) and GTV volume. CONCLUSIONS: Evolution in radiotherapy independently improved the prognosis of ASCC pts over years while reducing acute GI and skin toxicity. IMRT and daily 3D image guidance may to be considered standard of care in the management of ASCC. A combination of three pre-treatment MRI parameters such as low Signal Intensity (SI), high GLSZM’s LAHGLE, and GTV volume could be integrated in risk stratification to identify candidates for RT dose-escalation to be enrolled in clinical trials.